Informal Food Retail Trade in Ghanaian Cities - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This data is from a study conducted on informal food retail in three of Ghana’s cities – Accra, Kumasi and Tamale. The aim of the survey is to gather information on the livelihoods of these traders, the challenges they face, and the governance constraints they encounter, especially those selling different types of food products. Interviews with 1,214 informal food vendors – 474 in Accra, 516 in Kumasi, and 310 in Tamale – across 4-7 markets in each city, allow for a better understanding of the role of informal food vendors as a key component of agricultural transformation and food security, while also examining how their treatment by government officials affects their own food security and their ability to facilitate agricultural transformation. The survey is split into 11 survey modules: Sampling (SA) – preliminary characteristics of the informal food trader General Information (ID) – basic demographic, educational and household background information Employment (EM) – details on current job Business (BS) – information on business management and the associated fees paid to operate Taxes and Fees (TX) – range of fees and taxes paid and the benefits received from those payments Government Engagement (GE) – type and level of interaction between government officials and food traders Food Safety and Food Security (FS) – awareness of food safety and source of personal food Service Delivery and Accountability (SD) – services offered in the market and who could best deliver them Public Participation and Associational Membership (PP) – involvement in different associations and participation in public and community affairs Household Welfare (HW) – details on household assets and services Final (FI) – enumerator observations